PELESTARIAN CENDANA MELALUI POLA KONSERVASI LEKAT- LAHAN DI KABUPATEN BELU, NTT - Wawo, Albertus Husein (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2008)
Sandalwood (Santalum album L) is one of tropical plant in Indonesia that possess high economic value. Natural distribution of sandalwood centered in arid area of Nusa Tenggara Timur province and now a days this plant was groupped as rare plant. Many activities of in situ conservation for sandalwood have been carried out at some locations but did not give satisfaction in result yet. Ex situ conservation with utilize conservation on farm system is new model of plant conservation that involved local people. System of conservation on farm for sandalwood plant be defined as cultivation of sandalwood in the field/garden and home garden with involved farmers or local people. This system is known 2 models are ABC model (Model Agroforestri Berbasis Cendana) and Home garden as model of conservation area. Both models that mention had been applied in Belu regency, Nusa TenggaraTimur province.This research proposed to study the growth of sandalwood in ABC Model in the field/garden and in home garden as model of conservation area and to know the system of conservation on farm for sandalwood in Belu regency, Nusa Tenggara Timur province. ABC model was applied in 2 locations at Dirun Village (altitude at1000 m above sea level) and Teun Village (altitude at 500 m above sea level), while home garden as model of conservation area was applied at Teun village only.The Result shown that the rate of sandalwood growth in ABC model at Dirunvillage from first to third year between 60-70 cm in height per year, while sandalwood growth from third to fourth year has happened decreasing about 25 cm. The rate of sandalwood growth in ABC model at Teun Village from first to second year about 70-77 cm in height. The rate of sandalwood growth in home garden during 6 month after planting time about 4 -5 cm in height. Number of seedling still alife during 2 years after planting time in ABC model at Teun Village about 72%, during 4 yaers after planting time in ABC model at Dirun Village about 79%. While sandalwood seedling still alife during 6 months in home garden as model of conservation area about 75%. High persentation of seedling still alife with optimum rate of sandalwood growth have been found in this research because presence involvement of localpeople.